2004
DOI: 10.1021/bi0356911
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Scramblase 1 Is Imported into the Nucleus by a Receptor-Mediated Pathway and Interacts with DNA,

Abstract: Phospholipid scramblase 1 (PLSCR1) is a multiply palmitoylated, Ca(2+)-binding, endofacial plasma membrane protein originally identified by its capacity to accelerate transbilayer movement of membrane phospholipids. We recently reported that when palmitoylation of PLSCR1 does not occur, it is localized to the nucleus rather than the plasma membrane. Nuclear localization of PLSCR1 was also observed upon induction of its de novo synthesis by cytokines such as interferon alpha that activate the PLSCR1 gene. Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 19 publications
3
63
0
Order By: Relevance
“…Lastly, the nuclear localization of PLSCR1 in N1511 cells by day 7 of BMP/Ins treatment is similar to that observed in fibroblasts and suggests that PLSCR1 becomes depalmitoylated (67). The precise site of nuclear interaction is presently under investigation.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Lastly, the nuclear localization of PLSCR1 in N1511 cells by day 7 of BMP/Ins treatment is similar to that observed in fibroblasts and suggests that PLSCR1 becomes depalmitoylated (67). The precise site of nuclear interaction is presently under investigation.…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, by day 10, the effect of cholesterol depletion (i.e., membrane raft disruption) on scramblase activity was almost negligible, most likely due to the redistribution of PLSCR1 to the nucleus ( Figure 3B, as seen previously (67). Collectively, these results suggest that PS externalization is dependent on the relative activities of scramblase and ALPT, most likely in a cholesterol-dependent manner.…”
Section: Lipid Translocator Activities Change During Chondrocyte Matusupporting
confidence: 74%
“…ResiduesBen-Efraim et al (30) showed that PLSCR1 is imported into the nucleus by the importin ␣/␤ heterodimer (30) and the NLS sequence responsible for nuclear import comprises residues 257 GKISKHWTGI 266 . This sequence is less basic than classical SV40 NLS (the calculated isoelectric point is ϳ9.8 versus 11.38 for the SV40 NLS) and significantly more hydrophobic.…”
Section: A Poorly Basic Nls Enriched In Hydrophobicmentioning
confidence: 99%
“…In the cytoplasm PLSCR1 is localized mostly at the endofacial plasma membrane via multiple palmitoylations, where it binds calcium via a direct EF hand-like calcium binding domain (29). It was reported recently that PLSCR1 has the potential to enter the nucleus (30). This nuclear activity was observed either in the presence of inhibitors of palmitoyl-CoA, which block PLSCR1 anchoring to the plasma membrane, or by treatment with interferon ␣ (31), which is known to activate the PLSCR1 gene expression transcriptionally (32,33).…”
mentioning
confidence: 99%
See 1 more Smart Citation